Предмет: Алгебра,
автор: bkuvoter
упростите выражение (x-6)2×2x(-3x-6)
Ответы
Автор ответа:
0
Ответ:
Объяснение:
(x-6)2×2x(-3x-6)=(2x-12)×(-6x²-12х)=-12х³-24х²+72х²+144х=-12х³+48х²+144х=
= -12х(х²-4х-12)
Автор ответа:
0
(2x-12)(-6x2-12x)= -12x3-24x2+72x2+144x= -12x3+48x2+144
Потом можешь разделить на 12 и получится
-x3+4x2+12
Похожие вопросы
Предмет: Литература,
автор: Аноним
Предмет: Українська мова,
автор: irinaberezna999
Предмет: Английский язык,
автор: velushchak2011
Предмет: Математика,
автор: тоха162